Effect of Heat Treatment on Microstructures and Mechanical Properties of a Novel β-Solidifying TiAl Alloy - Cui, Ning (Materials (Basel), 2019)
The effect of heat treatment on the microstructures and mechanical properties of a novel β-solidifying Ti–43Al–2Cr–2Mn–0.2Y alloy was investigated. A fully lamellar (FL) microstructure with a colony size of about 100 μm was obtained by heat treatment at 1320 °C/10 min/furnace cooling (FC). A duplex (DP) microstructure with globular γ grains and γ/α(2) lamellae was obtained by heat treatment at 1250 °C/4 h/FC. The residual hard–brittle β(0) phase was also eliminated after heat treatment. The mechanical properties of the β-solidifying TiAl alloy depended closely on the heat treatment. The FL alloy had better fracture toughness, and the fracture toughness (K(IC)) value was 24.15 MPa·m(1/2). The DP alloy exhibited better ductility, and the room temperature (RT) elongation of the alloy could reach 1%. The elongation of the alloy with different microstructures sharply increased when the temperature increased from 700 to 750 °C, indicating that the microstructure had no effect on the ductile–brittle transition temperature of the β-solidifying TiAl alloy. The fracture morphologies of different tensile specimens were observed. Interlamellar and translamellar fractures were the main fracture features of the FL alloy. Intergranular, translamellar, and interlamellar fractures were the main fracture features of the DP alloy.